A Review on the Role of miR-1246 in the Pathoetiology of Different Cancers - Ghafouri-Fard, Soudeh; Khoshbakht, Tayyebeh; Hussen, Bashdar Mahmud; Taheri, Mohammad; Samadian, Mohammad (Frontiers in Molecular Biosciences, 2022)
miR-1246 is a microRNA firstly recognized through application of a high throughput sequencing technique in human embryonic stem cells. Subsequent studies have shown the role of this microRNA in the carcinogenesis. miR-1246 has been found to exert oncogenic roles in colorectal, breast, renal, oral, laryngeal, pancreatic and ovarian cancers as well as melanoma and glioma. In lung, cervical and liver cancers, studies have reported contradictory results regarding the role of miR-1246. miR-1246 has been reported to regulate activity of RAF/MEK/ERK, GSK3β, Wnt/β-catenin, JAK/STAT, PI3K/AKT, THBS2/MMP and NOTCH2 pathways. In addition to affecting cell cycle progression and proliferation, miR-1246 can influence stemness and resistance of cancer cells to therapeutics. In the current review, we describe the summary of in vitro and in vivo studies about the influence of miR-1246 in carcinogenesis in addition to studies that measured expression levels of miR-1246 in clinical samples.